Role of photosystem II activity in salt tolerance of Panicum antidotale and Panicum turgidum: Insights from chlorophyll a fluorescence analysis on excised leaf - Muhammad Javed; Muhammad Iqbal; Habib-ur-Rehman Athar; Zafar Ullah Zafar; Fahim Arshad; Muhammad Ashraf (Journal of Animal and Plant Sciences, 2024)
Salt stress limits photosynthetic capacity of plants by disturbing thylakoidal reactions. Chlorophyll fluorescence measurements help in measuring the extent of photosystem-II (PSII) photodamage. Panicum antidotale (P. antidotale) and Panicum turgidum (P. turgidum) are potential fodder grasses, adapted to a variety of environmental stresses like salinity and drought. In the present study, photosynthetic performance was assessed by chlorophyll a fluorescence kinetic analysis of excised leaves of these two grass species immersed in varying concentration of NaCl (0, 250, 500 and 1000 mM NaCl) after 24 hours. Salt stress decreased chlorophyll fluorescence at J, I and P steps indicating reduced efficiency of electron transfer at PSII and from PSII to PSI. In addition, salt induced increase in Fo (11% in P. antidotale; 29% in P. turgidum) along with reduction in Fm indicated PSII photoinhibition at the donor end. Performance index (PIABS) and quantum yield of PSII were decreased in excised leaves of both Panicum species with increasing salt levels. However, P. antidotale had greater PIABS (1.08) and quantum yield of PSII (0.72) than in P. turgidum (0.47 and 0.57 respectively), which is associated with better management in absorption (0.84% as compared to 12.4% in P. turgidum), trapping and electron transport or better management of PSII excitation pressure under salt stress. Activity of PSII measured as PIABS and some related JIP-test parameters can be used as potential indicators of salt tolerance. So increasing salinity stress affected primary photochemistry of PSII in excised leaves of both grass species but adverse effect of salt stress on PSII photochemistry was greater on P. turgidum than that of P. antidotale. It is suggested that assessment of fast chlorophyll a kinetic analysis on excised leaves of different species/cultivars may help in screening and selection for salt tolerance.
Keywords: Salinity stress; grasses; chlorophyll fluorescence; electron transport chain; photosystem II